2017
DOI: 10.3390/socsci6010013
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Military Cultural Competence among Civilian Care Providers: Learning through Program Development

Abstract: Abstract:Military veterans and their families belong to a unique subculture. Several studies have identified the need for helping professionals to attain military cultural competence in order to practice more effectively. In order to address this need, a Midwestern state created a military culture certificate program (MCCP). The process of developing this program is described. Eighty-two participants of the MCCP completed a pretest survey assessing their knowledge, awareness, and self-confidence in working wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…Veterans are more likely to report having greater access to care and excellent/very good health. Yet, they face a higher chronic disease bur-Advances in Applied Sociology den and report higher rates of diagnoses of depression, past-year mental illness, and past-year suicidal thoughts than civilian women (Nedegaard & Zwilling, 2017). Female Veterans have military exposures that contribute to disproportionate disparities compared to their civilian peers, consisting of adverse reproductive health outcomes, a high-risk population for adverse pregnancy outcomes, rape and sexual assaults, and mental health conditions such as depression and PTSD (Katon et al, 2018).…”
Section: Disparities In Mental Health Treatmentmentioning
confidence: 99%
“…Veterans are more likely to report having greater access to care and excellent/very good health. Yet, they face a higher chronic disease bur-Advances in Applied Sociology den and report higher rates of diagnoses of depression, past-year mental illness, and past-year suicidal thoughts than civilian women (Nedegaard & Zwilling, 2017). Female Veterans have military exposures that contribute to disproportionate disparities compared to their civilian peers, consisting of adverse reproductive health outcomes, a high-risk population for adverse pregnancy outcomes, rape and sexual assaults, and mental health conditions such as depression and PTSD (Katon et al, 2018).…”
Section: Disparities In Mental Health Treatmentmentioning
confidence: 99%
“…Civilian providers may be competent professionally but lacked understanding of ADSM's military experiences, challenges, and language, which can negatively affect active duty status and may result in ADSMs choosing not to seek mental health care. Knowledge deficits related to understanding acronyms and military language, rank and organizational structure, the impact of deployment, military ethical issues, knowledge about services available, and pertinent political and historical influences are often a significant reason why ADSM patients discontinue treatment with community-based providers after a single visit (Nedegaard & Zwilling, 2017).…”
Section: Table 3 (Continued)mentioning
confidence: 99%
“…A correlational analysis identified the relationships between the subscales of "identity", and the outcome variables differed in strength and direction depending on the form of identity, supporting a multidimensional structure of military identity and culture. Research to promote military, cultural competence among civilian care providers, Nedegaard, & Zwilling (2017) identified that assessments must measure military-specific knowledge to evaluate cultural competence for the Veteran population.…”
Section: Introductionmentioning
confidence: 99%